2009
DOI: 10.1089/dia.2008.0131
|View full text |Cite
|
Sign up to set email alerts
|

Exubera Inhaled Insulin in Patients with Type 1 and Type 2 Diabetes: The First 12 Months

Abstract: Our 12-month audit data demonstrate that the initiation of inhaled insulin in this difficult-to-treat group of patients resulted in a significant improvement in glycemic control. The subsequent withdrawal of an alternative and acceptable form of insulin treatment now presents a renewed challenge for our patients and healthcare professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Likewise, PEGylation and liposomes continue to extend their applications with new drugs, yet primarily for injection [84,85]. It should be recognized, however, that even inhaling a natural peptide, insulin (i.e., Exubera), has required enormous cost and time in both preclinical and clinical studies, to ensure the safety of its chronic use in patients with diabetes, including antibody production, lung function and risk of lung cancer, in addition to clinical therapeutic benefits and patient/market acceptance [9, [86][87][88]. Hence, new biotherapeutics for systemic delivery via inhalation must likewise follow this rigorous path paved by Exubera to ensure their safety and acceptance in clinical use.…”
Section: Future Perspectivementioning
confidence: 99%
“…Likewise, PEGylation and liposomes continue to extend their applications with new drugs, yet primarily for injection [84,85]. It should be recognized, however, that even inhaling a natural peptide, insulin (i.e., Exubera), has required enormous cost and time in both preclinical and clinical studies, to ensure the safety of its chronic use in patients with diabetes, including antibody production, lung function and risk of lung cancer, in addition to clinical therapeutic benefits and patient/market acceptance [9, [86][87][88]. Hence, new biotherapeutics for systemic delivery via inhalation must likewise follow this rigorous path paved by Exubera to ensure their safety and acceptance in clinical use.…”
Section: Future Perspectivementioning
confidence: 99%
“…The increasing interest in clinical use of inhaled insulin formulations that could lead to very high levels of insulin in the lung also illustrates the need for focused studies on insulin and lung health, given that there have been reports of negative effects on lung function with a previous formulation, Exubera (Pfizer) (5).…”
mentioning
confidence: 99%
“…Teeter and Riese (14), whose work is extensively cited by Wolff et al, found that both subcutaneous and inhaled insulin led to a decline in FEV 1 , more so for inhaled insulin. Such a decline in FEV 1 has been consistently replicated in other studies (1). It is critical to note that spirometry is a poor test for distal airway disease and even small declines in FEV 1 may be associated with significant distal airway changes.…”
Section: To the Editormentioning
confidence: 66%